The manifestation of privilege: A critical discourse analysis of the Indonesian circular letter on health protocols for international travel - Kintani, Naomi Halida; Widyastuti, Susana (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2023)
Taking the principles of critical discourse analysis favoring issues on unequal power relations, this discourse study attempts to disclose the manifestation of privilege in government regulations. To do so, it combines the principles of Systemic Functional Grammar and CDA by explicating the results of transitivity analysis on the legal text within relevant socio-political context. The data were the clauses in Circular Letter No. 26/2021 enacted by the Indonesian government on Health Protocols for International Travel during the COVID-19 Pandemic. The results show that, in terms of transitivity, the circular letter includes material, relational, verbal, and mental process, which serve to show the details on health protocols to be adhered by travelers, to describe the criteria of travelers who are given special provisions and of the countries being temporarily banned from entering Indonesia, to report the health condition of travelers, and to show the need of medical assistance. The material and relational processes demonstrate the form of privileges, namely dispensation from quarantine implementation and the exemption from Indonesia travel restriction. The relational process shows the particular privileged groups, including the state officials, delegates of economic cooperation, and well-known figures. It is embedded in the circular letter that what are deemed beneficial for the political elites and the country's economic are somehow not in line with the public interest.